The impact of staff training and financial regulations on financial sustainability of microfinance institutions in Tanzania: A case of Morogoro municipality. - Chamshama, Shesaa Shabani (Mzumbe University, 2024)
A dissertation submitted Mzumbe University as a partial fulfilment of the requirements for the award of degree of Masters of Business Administration Corporate management (MBA-CM) of Mzumbe University.